Peran Roh Kudus Dalam Pertumbuhan Gereja Menurut Kitab Kisah Para Rasul - Yovianus Epan; Asih Rachmani Endang Sumiwi (SANCTUM DOMINE: JURNAL TEOLOGI, 2022)
The new testament history of the apostles records that it is after Pentecost. The Lord's church is organism forged through the preaching of the apostles and the believers and then formed a fellowship within it. The bible records the early appearance of communion on ACTS 2:41-47 as a result of experiencing repentance from the apostle Peter's talk after Pentecost received by the apostles in Jerusalem's attic. The growth of the church at that time was based on the work of the holy ghost through the apostles and believers through the preaching being preached there were many converts and then in forming communities of believers. Such communion results from the work of the holy ghost in the lives of believers, so the role of the holy ghost has the effect of growth in the church both organisms are capable of forming a vast communion of the Lord's congregation.